Thirty-five years of eye banking in Hong Kong - a metamorphosis and a commitment renewed (Hong Kong Journal of Ophthalmology, 1997)
The Hong Kong Eye Bank and Research Foundation (HKEBRF) was established 35 years ago. Its primary objective was to serve as a collecting and distributing center of corneas for transplantation by eye surgeons in Hong Kong. In the early years, its call for eye donation was not met with any success and it has been rendered into a passive liaison office. However, in the last few years, a change in the medical environment, in the patients' needs and surgeons' demand for corneal tissue, has ushered the HKEBRF into a new era of an active Eye Tissue Laboratory (ETL). The ETL of the HKEBRF, with a modified and assertive approach to eye donor recruitment, is ready to make good the Eye Bank's original commitment of promoting and effecting eye donations.